Chemical Composition and Biological Activities of Anethum graveolens L. Essential Oil from Algeria. Issue 4 (4th July 2022) - Benlembarek, Khaoula; Lograda, Takia; Ramdani, Messaoud; Figueredo, Gilles; Chalard, Pierre
Abstract: Anethum graveolens commonly known as dill plant is a very important shrub which is widely acknowledged in traditional and modern medicine for its capacity to treat colic pain and flatulence. The purpose of this work is the study of the chemical composition and the evaluation of antibacterial, antifungal and antioxidant activities of A. graveolens essential oil. The samples were collected from the chellal region in Algeria and submitted to hydrodistillation. The essential oil extracted was analyzed by GC and GC/MS. The antibacterial and antifungal activities were tested by the disc diffusion method; seven bacteria and four phytopathogenic fungi were used. The evaluation of the antioxidant activity was carried out by the 2, 2-diphenyl-1-picrylhydrazyl scavenging method. The results of the GC and GC/MS analysis allowed the identification of 22 components with carvone(34.33%), α-phellendrene (22.03%), dill ether (18.84%), limonene (6.93%) and dill apiol (5.01%) as major components. The results of the disc difusion method show that Anethum graveolens essential oil exhibits strong antibacterial activity against Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa and moderate antifungal activity against Fusarium graminum and Alternaria alternata . The pure essential oil showed a moderate antioxidant activity with inhibition percentages of 49.93 ± 4.58%. This study highlights the importance of chemical constituents of A. graveolens essential oil which possesses important pharmacological effects on different pathogenic strains and could be used as substitute for synthetic antimicrobial drugs in pharmaceutical industries.